Unpacking multi-level governance of antimicrobial resistance policies: the case of Guangdong, China. Issue 9 (1st July 2022) - Chan, Olivia Sinn Kay; Wernli, Didier; Liu, Ping; Tun, Hein Min; Fukuda, Keiji; Lam, Wendy; Xiao, YongHong; Zhou, Xudong; Grépin, Karen A
Abstract: Against the backdrop of universal healthcare coverage and pre-existing policies on antimicrobial use, China has adopted a state-governed, multi-level, top-down policy governance approach around an antimicrobial resistance (AMR) national action plan (NAP). The Plan relies on tightening control over antimicrobial prescription and use in human and animal sectors. At the same time, medical doctors and veterinarians operate in an environment of high rates of infectious diseases, multi-drug resistance and poor livestock husbandry. In exploring the way that policy responsibilities are distributed, this study aims to describe how Guangdong as a province adopts national AMR policies in a tightly controlled public policy system and an economy with high disparity. We draw on an analysis of 225 AMR-relevant Chinese policy documents at the national and sub-national levels. We adopt a multi-level governance perspective and apply a temporal sequence framework to identify and analyse documents. To identify policy detail, we conducted keyword analysis using the Consolidated Framework for Implementation Research (CFIR) on policies that conserve antimicrobials. We also identify pre-existing medical and public policies associated with AMR. Our findings highlight the emphasis and policies around antimicrobial use regulation to address AMR in China.